Media Video Feature Penunjang Promosi Pariwisata Kabupaten Pati – Jawa Tengah - Slamet Riyanto; Dany Setiawan; Aviv Rivaldi (CICES (Cyberpreneurship Innovative and Creative Exact and Social Science), 2017)
The tourism sector of the economy section of some of the country's potential and the preoritas development of komudite expected to State financial input, especially for developing countries like Indonesia. Especially in the area of Pati, which has a wide area with potential for cultivation, some of the results varied historical heritage, culture and community kehiduapan a unique and natural beauty that can serve as the local tourist attraction and abroad. Lately the multimedia world is already very familiar ditelinga public. The importance of multimedia delivery of information in the spur of the berkreatifitas designer to create forms of media information more communicative and more efficient that can be attractive to people. Similarly the Tourism District of Central Java province in Starch promotes the garrison prosecuted can be showing something interesting about potential-potential of the area through a form of media can indulge the senses of vision and hearing senses. One of them is with the media featured the cast in a video as a Messenger of information short but very interesting for people to see it. Because of the uniqueness of the dimensions, so that it can be accepted as one of the audio visual media are the most popular. In addition to this, there is a wide range of visual effects computer graphics technique called Computer Generated Imagery (CGI). CGI to process photography, animation is rooted in the world of image and video editing as well as a mix of photography, animation and video editing became an attractive display. Expected with the media featured this Tourism Pati can display an effective promotion and attractive to the wider community to visit attractions that exist in Pati.